Shear and Tensile Strengths of The Bonded Bracket to The Ceramic Surface - Hussain A Obaidi; Muzahim H Hanna (University of Mosul, College of Dentistry, 2010)
Aims: To assess the shear and tensile strengths of the bonded bracket to the treated porcelain surface with hydrofluoric acid, and microetcher. Materials and Methods: The sample included 30 specimens of porcelain blocks (6 mm in diameter and 2mm thickness). The sample was grouped into three groups, 10 specimens for each group. The groups were: acid etched, microetched at 5mm distance, and micro-etched at 10mm distance. Stainless steel brackets (Roth System) were bonded to the treated porcelain surfaces using light cure Orthodontic composite resin. All the groups were thermocycled. The shear and tensile bond strengths of the bonded bracket were measured by using the shear and tensile Univer-sal testing machine. The results were analyzed statistically; that include: Descriptive, ANOVA and Duncan's multiple analysis range testes at p≤ 0.05 significant level. Results: It was revealed that the shear and tensile bond strength values of the bonded brackets to porcelain surface treated with microet-cher at 5mm distance was greater significantly than that treated with acid etch, and microetched at 10mm distance. Conclusions: The porcelain surface treated with microetcher is strongly recommended for bonding orthodontic brackets.